The adsorption behavior of surfactants on mineral surfaces in the presence of electrolytes – A critical review. (1st June 2018) - Chang, Ziyong; Chen, Xumeng; Peng, Yongjun
Graphical abstract: Highlights: Electrolytes affect the solubility and aggregation of surfactants in solution. Electrolytes change the adsorption behavior of surfactants on solids. Electrolytes cause the structural transition of adsorbed surfactant layers on solids. Abstract: How saline water affects the adsorption of surfactants on mineral surfaces and the subsequent flotation behavior is still unknown despite the widespread application of saline water in mineral flotation. However, in the field of surfactants, the effect of electrolytes on the adsorption of surfactants on solids has been well studied. This paper presents a comprehensive review of surfactant adsorption on solids in the presence of electrolytes based on the previous research findings. The review shows that the presence of electrolytes significantly influences the solubility and aggregation of surfactants in the liquid phase either through electrostatic interactions or "salting-in" and "salting-out" effects. In the process of surfactant adsorption on solids, electrolytes influence the adsorption density of ionic surfactants and non-ionic surfactants by affecting the surfactant-surfactant interactions and surfactant-solid interactions. Once surfactants adsorb on solids, electrolytes modify the structure and morphology of adsorbed surfactant layers and even induce the structural transition. This paper provides a thorough understanding of surfactant adsorption on solids in the presence of electrolytes and guides the application of surfactants in mineral flotation using saline water.